The Impact of Cancer Caregiving on Cancer Caregivers: Stories of Lives in Transition - (:unkn) unknown (My University, 2013)
The purpose of the study was to examine the impact of cancer caregiving on primary caregivers, exploring their personal narratives looking back on the entire experience from diagnosis, through treatment, and beyond. Caregiving is associated with exacerbation of stress-related disorders such as hypertension and heart disease and may also be associated with increased mortality rates. Transitions theory served as the conceptual framework for the study. Eleven adult caregivers, pre-retirement age, each participated in two semi-structured interviews. Caregivers were recruited from a community cancer resource center and were purposively selected to achieve maximum variation in terms of outcome of cancer treatment. The sample included 8 females and 3 males; there were 3 husbands, 6 wives, and 2 daughters. Caregivers provided care for patients with a variety of cancer types and a variety of treatment outcomes, from cancer free with sequelae to deceased. Each caregiver interview recording was transcribed, and preliminary examination of each transcript helped guide subsequent interviews. NVivo9 software was used to assist with data management. Data saturation was achieved. Narrative within-case analyses as well as thematic analysis were used to address research questions. Thematic analysis resulted in seven themes: Burden: The Load that Never Ends; Disconnectedness and Isolation: The Invisible Person; Helplessness and Loss of Control: Tied to This Ride; Dealing with the Healthcare System; Role Disruption: Spinning the Plates; Loss, Change, and Grief: Reaction to the Whole; and Carrying Forward with Scars: New Priorities and Permanent Change. All of the caregivers changed their employment or social responsibilities due to the demands of caregiving. Themes were present in different parts of the cancer trajectory and in differing intensities in all interviews. Findings included disconnectedness and isolation as a central feature of cancer caregiving, plus significant grief present through the cancer trajectory, especially in the post-treatment phase. Furthermore, the experience of cancer caregiving remained one of significant impact years after treatment had ended. Successful transitioning requires connectedness and mastery, but participants in this study identified that their caregiving trajectories were full of isolation, grief, burden, and helplessness. Many suggested the need for support, even though they tended to deny their own physical and emotional needs while caregiving. Healthcare professionals can help by providing information, support, listening, and grief counselling. Research is needed on interventions that may reduce isolation, helplessness, and burden for caregivers.
Keywords: Cancer Caregiver; Caregiving; Narrative; Qualitative; Transition Theory